Reducing barriers to promote engagement and retention in adolescent substance use treatment: results from a quality improvement evaluation - Chen, Eileen; Seely, Hayley D.; Thurstone, Christian (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction: Although research on the development and efficacy of adolescent substance use treatment has made recent strides, many models do not translate into practice, especially when working with underserved youth who often face barriers to treatment. Meal incentives, rolling admission, and transportation assistance may be promising approaches to decrease barriers, thereby increasing treatment engagement, retention, and completion. The purpose of this evaluation was two-fold: 1) to examine treatment engagement amongst diverse, underserved youth in an intensive outpatient program for substance misuse in an urban metropolitan area, and 2) to investigate the role of meal incentives, rolling admission, and transportation assistance in youth engagement. Methods: The intervention was 8 weeks of Acceptance and Commitment Therapy and trauma-focused group intervention, combined with contingency management, meal incentives, and transportation assistance. Treatment engagement, retention, and completion was compared against selected demographic variables (i.e., race and insurance coverage) and at three phases of program implementation: cohort admissions with transportation assistance (phase 1); rolling admissions with transportation assistance (phase 2); and rolling admissions with transportation assistance and meal incentives (phase 3). Data was analyzed using two-way ANOVAs; identified interactions were probed. Results: Participants were 110 adolescents (ages 13-17) consecutively admitted to an intensive outpatient substance treatment program. Racial identities of participants were 40.0% Latinx, 3.6% Black, 0.9% American Indian or Alaska Native, 6.4% two or more races, and 49.1% White. A total of 67 of 110 (60.9%) youth had state-funded Medicaid or no insurance. Of the youth that engaged in treatment across all implementation phases, 68.7% were provided transportation assistance. Analyses illustrated no difference in outcomes based on selected demographic variables. The percentage of youth completing treatment was 22.7% and the average number of groups attended was 6.32 (SD = 6.49). Results showed a significant improvement in outcomes with the implementation of incentives such that engagement and retention in treatment was significantly higher for those in phase 3 compared to those in phase 1 (p < .001) and phase 2 (p = .021). Discussion: This evaluation shows that previously documented health disparities in substance treatment engagement and retention are not found when certain barriers are addressed.